Observasi Metode Pembelajaran PPKn Di SMP Negeri 35 Medan - Dewi Romantika Tinambunan; Esra Natasya Sitepu; Ivana Theo Philia; Jekson Saragih; Laras Sati Sintania; Ture Ayu Situmeang (International Forum of Researchers and Lecturers, 2023)
This research is entitled